2010
DOI: 10.3762/bjnano.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of supported magnetic nanoparticles prepared by reverse micelles

Abstract: SummaryMonatomic (Fe, Co) and bimetallic (FePt and CoPt) nanoparticles were prepared by exploiting the self-organization of precursor loaded reverse micelles. Achievements and limitations of the preparation approach are critically discussed. We show that self-assembled metallic nanoparticles can be prepared with diameters d = 2–12 nm and interparticle distances D = 20–140 nm on various substrates. Structural, electronic and magnetic properties of the particle arrays were characterized by several techniques to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 105 publications
2
59
1
1
Order By: Relevance
“…6. Recently, we have shown that this linear behaviour is obtained for Co NPs on Si/SiO 2 substrates at T = 10 K with interparticle distances comparable to those in the present samples [11]. The experimental curves for different annealing temperatures closely resemble each other and all are found to be near to the Stoner–Wohlfarth line.…”
Section: Resultssupporting
confidence: 83%
“…6. Recently, we have shown that this linear behaviour is obtained for Co NPs on Si/SiO 2 substrates at T = 10 K with interparticle distances comparable to those in the present samples [11]. The experimental curves for different annealing temperatures closely resemble each other and all are found to be near to the Stoner–Wohlfarth line.…”
Section: Resultssupporting
confidence: 83%
“…This can be very sensitive to little changes of the lattice constant, explaining why only specific lattice distortions give rise to the desired high anisotropies in CoFe3440 or CoPt and FePt4142 alloys. The interline anisotropies reported here are by an order of magnitude larger than the ones reported for Co double-layer islands decorated by Au21.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation was triggered by the experience that nanoparticles fabricated in real world experiments unfortunately fail to meet this expectation [28,29]. The particles can be produced in wet chemical experiments [20,30,31] or also frequently via the gas phase production route [32][33][34][35][36], which allows to avoid the presence of organic ligands.…”
Section: Introductionmentioning
confidence: 99%